A systematic review of oral retinoids for treatment of acneiform eruptions induced by epidermal growth factor receptor inhibitors. Issue 5 (3rd March 2022) - Bierbrier, Rachel; Lam, Megan; Pehr, Kevin
Abstract: Epidermal growth factor receptor inhibitors (EGFRi) are now standard of care in patients with EGFR mutations in non‐small cell lung cancer (NSCLC) and are increasingly being used in other EGFR mutated cancers, including gastrointestinal, and head and neck. However, EGFRi are well known to cause acneiform eruptions, which are shown to positively correlate with tumor response to treatment, but may be severe enough to cause interruption of their treatment. Although most guidelines call for the use of tetracyclines to treat these acneiform eruptions, there is mounting evidence for the use of systemic retinoids instead. The objective of this review is to summarize available data on the use of systemic retinoids for management of acneiform eruptions on EGFRi. This study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. MEDLINE and EMBASE were searched from database inception until December 10th, 2021. All articles were screened and relevant data extracted independently in duplicate by two reviewers. In total, 16 case reports, case series and retrospective reviews were included. Forty‐three patients were treated with retinoids for their acneiform eruption due to EGFRi. The majority (77%) noted moderate to significant improvement after treatment initiation with minimal adverse events (16%). The findings of this systematic review suggest that systemic retinoids are a safe and effective therapy for the management of acneiform eruptions induced by EGFRi.